UMP PhD student excel in national level 3MT Competition - Kalpana, Ramachandran (2021)
KUANTAN, 10 June 2021 - A doctorate student from the Faculty of Mechanical and Automotive Engineering Technology (FTKMA), Universiti Malaysia Pahang (UMP), Mohd Hilmy Naim Mohd Yakin, was announced the winner for the national-level Three Minute Thesis (3MT) competition in the Technology and Engineering category.